2000
DOI: 10.1159/000007778
|View full text |Cite
|
Sign up to set email alerts
|

Severity of HCV-Induced Liver Damage Alters Glucose Homeostasis in Noncirrhotic Patients with Chronic HCV Infection

Abstract: Background/Aims: To investigate the link between hepatitis C infection and glucose intolerance, we measured insulin sensitivity, glucose effectiveness and β-cell secretion in noncirrhotic HCV-infected patients with normal glucose tolerance according to WHO criteria as assessed by oral glucose tolerance tests. Methods: Glucose, insulin and C-peptide data from frequently sampled intravenous glucose tolerance tests were analyzed using the minimal modeling technique for glucose and C-peptide to determine insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 40 publications
(66 reference statements)
1
18
1
Order By: Relevance
“…HCV has been identified in bile ducts within the liver [35], and HCV RNA was detected in pancreatic tissue harvested from patients with acquired immune deficiency syndrome [36]. The production of cytokines during HCV-induced inflammatory processes in liver tissue could explain the progressive impairment of b-cell function with increasing liver damage [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV has been identified in bile ducts within the liver [35], and HCV RNA was detected in pancreatic tissue harvested from patients with acquired immune deficiency syndrome [36]. The production of cytokines during HCV-induced inflammatory processes in liver tissue could explain the progressive impairment of b-cell function with increasing liver damage [12].…”
Section: Discussionmentioning
confidence: 99%
“…Konrad et al [12] suggested that insulin resistance in patients with CH due to HCV infection (CHC) is caused by the liver disease itself. In contrast, Petit et al [13] demonstrated that insulin resistance in nondiabetic HCV-infected patients correlates with the staging of liver fibrosis but may occur at an early stage in the course of HCV infection, even in nondiabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…the fasting insulin and a decrease in insulin sensitivity have been observed in HCV-infected subjects with a moderate or severe degree of hepatic fibrosis (75,134,135). However, HCV-infected patients without fibrosis (fibrosis stage 0) also present higher insulin resistance than patients with primary biliary cirrhosis with different degrees of hepatic fibrosis (fibrosis stages 1-3) and healthy individuals (36).…”
Section: Insulin Resistance and Liver Fibrosis -An Increase Ofmentioning
confidence: 99%
“…Alternatively, insulin resistance has been described as an independent factor in predicting the presence of hepatic fibrosis in HCV-infected patients (36). In fact, several studies have reported that both insulin resistance and diabetes can adversely affect the course of chronic hepatitis C leading to enhanced steatosis and liver fibrosis (24,28,95,96,100,101,134) and even increase the risk of hepatocellular carcinoma (136,137). Notably, Romero-Gó mez et al (138) and D'Souza et al (139), have recently shown that insulin resistance is an independent predictor of a poor response to antiviral therapy in chronic hepatitis C infection.…”
Section: Insulin Resistance and Liver Fibrosis -An Increase Ofmentioning
confidence: 99%
“…For example, HCVinduced cirrhosis could increase the occurrence of diabetes merely by an alteration in glucose homeostasis [17]. Consequently, studies have confirmed the association between HCV and type 2 diabetes, even after excluding cirrhotic patients [8][9][10]. Moreover, in population-based cohort studies, undiagnosed end-stage liver disease is highly improbable.…”
Section: Diabetes and Hepatitis C Infection: A Specific Epidemiologicmentioning
confidence: 99%